PENINGKATAN PENGETAHUAN TENTANG MANFAAT BAWANG PUTIH DALAM PENCEGAHAN KECACINGAN DI LINGKUNGAN IV KELURAHAN BARU LADANG BAMBU MEDAN TUNTUNGAN - Napitupulu, David Sumanto; Ritonga, Muhammad Azli; Arisandi, Ermawaty; Sitepu, Aprilita Br; Tarigan, Rica vera Br; Lumban Gaol, Rusmauli (Universitas Aufa Royhan Di Kota Padangsidipuan, 2026)
One of the residents of environment IV Medan Tuntungan, namely a mother, said that her child had worms, characterized by a large stomach and lots of worms in his stomach. This incident illustrates that in the area the worm infestation rate is already high. The initial survey results of the community service team also saw children playing in the dirt in the afternoon without washing their hands with soap. The aim of this health education is to determine the level of knowledge of parents (participants) about the benefits of garlic and worms. The method used was a direct presentation to 10 participants in the Baru Ladang Bambu Subdistrict, Medan Tuntungan. Evaluation has been carried out by providing pre test and post test. The result of the evaluation before the health education was carried out were that the majority of participants’ knowledge level was in the good category, only 2 person (20%), meaning that only a few understood about garlic and worms. After health education was carried out, there was an increase in knowledge from 2 person to 4 person or 40%. Comparison of participants’knowledge before and after health education was carried out showed an increase participants’ knowledge of 100% for the good category. This health education activity succesfully increased participants’ knowledge about worm infestation and the use of garlic in preventing worm infestation.